Increasing flood risk awareness and warning readiness by participation – But who understands what under 'participation'?. (15th April 2021) - Fekete, Alexander; Aslam, Atif Bilal; de Brito, Mariana Madruga; Dominguez, Iris; Fernando, Nishara; Illing, Christian J.; KC, Apil K; Mahdavian, Farnaz; Norf, Celia; Platt, Stephen; Santi, Parana Ari; Tempels, Barbara
Abstract: Participation is an often-demanded process in disaster risk reduction (DRR). However, it is often unclear who understands what under this term. International organizations such as the United Nations have promoted participation in their DRR strategies since the 1980s, but further research is needed on its opportunities and limitations. Here we highlight what is understood by participation according to different actors and various international contexts. This study was motivated by a workshop where flood-risk and resilience experts from 14 countries perceived the nature of participation and the lack of its implementation differently. To unravel the multitude of these perspectives, 27 expert interviews were conducted in seven countries: Belgium, Germany, Indonesia, Iran, Nepal, Pakistan and Peru between March and August 2020. Results show that constraints on the conduction of participation are not only related to the specific country context but differ even within countries. Limitations such as capacities and willingness to participate as well as the role and importance of participation are common issues across the investigated contexts and countries.